2000
DOI: 10.1115/1.1424299
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of a Computer Hard Disk Drive Under Shock

Abstract: Shock of computer hard disk drives (HDD) in both portable and desktop computers is a common problem. Shock of an HDD can occur during installing the HDD into the computer, HDD testing, HDD handling, and so forth. It is important to identify key design parameters to improve HDD shock performance. This paper presents the finite element studies of a HDD under a non-operational linear drop shock. A complete HDD model is built in ANSYS finite element package. GP commands are used to apply the preload and define the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Lee et al (2001) developed a single-degree-of-freedom (SDOF) model for predicting the shock behavior of the suspension. Lin (2002) studied the effects of various mechanical parameters on shock resistance by simulating the non-operational shock response of a drive, and the results revealed that increasing the actuator and base plate stiffnesses improved the shock performance. In the research of Gao et al (2005), a flexible multibody dynamics formulation was developed to analyze the vibration of the voice coil motor (VCM-actuator) assembly and the disk-spindle assembly.…”
Section: Introductionmentioning
confidence: 98%
“…Lee et al (2001) developed a single-degree-of-freedom (SDOF) model for predicting the shock behavior of the suspension. Lin (2002) studied the effects of various mechanical parameters on shock resistance by simulating the non-operational shock response of a drive, and the results revealed that increasing the actuator and base plate stiffnesses improved the shock performance. In the research of Gao et al (2005), a flexible multibody dynamics formulation was developed to analyze the vibration of the voice coil motor (VCM-actuator) assembly and the disk-spindle assembly.…”
Section: Introductionmentioning
confidence: 98%
“…A correlation between linear drop test and tilt drop test was set up. Lin [7] developed a two-head HDD model in ANSYS. A semi-sine acceleration pulse is applied to the base of the HDD, the duration of the semi-sine pulse, the thickness of the disk and the stiffness of the bearing were studied for the non-operating shock.…”
Section: Introductionmentioning
confidence: 99%
“…HDD was created by Lin (2002) using ANSYS. In that analysis, the effect of shock on a non-operational HDD was studied.…”
Section: Introductionmentioning
confidence: 99%